Battling Covid-19 with Artificial Intelligence: What Will Work in Africa? - Abejide Ade-Ibijola; Charis Harley (The Thinker)
Can AI really help? Many researchers and industry experts working in Artificial Intelligence (AI) have claimed that AI holds the answers to the past, present, and future difficulties faced by humankind.